2017
DOI: 10.3748/wjg.v23.i15.2731
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal and interval cancers of the Colorectal Cancer Screening Program in the Basque Country (Spain)

Abstract: AIMTo assess proportions, related conditions and survival of interval cancer (IC).METHODSThe programme has a linkage with different clinical databases and cancer registers to allow suitable evaluation. This evaluation involves the detection of ICs after a negative faecal inmunochemical test (FIT), interval cancer FIT (IC-FIT) prior to a subsequent invitation, and the detection of ICs after a positive FIT and confirmatory diagnosis without colorectal cancer (CRC) detected and before the following recommended co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 26 publications
6
36
0
Order By: Relevance
“…As observed in other studies, participation in CRCSP is influenced by age and sex, with participation in Initial screening-first invitation being higher in women (Portillo et al, 2013;Clarke et al, 2015;Molina-Barceló et al, 2014) and in persons aged 60-69 years than in persons aged 50-59 years (Salas et al, 2014). In contrast, adherence to screening among persons with previous participation showed differences by age but not by sex, with lower participation among young men and women, as reported in other studies (Ricardo-Rodrigues et al, 2015;Steele et al, 2010).…”
Section: Accepted Manuscriptsupporting
confidence: 58%
See 1 more Smart Citation
“…As observed in other studies, participation in CRCSP is influenced by age and sex, with participation in Initial screening-first invitation being higher in women (Portillo et al, 2013;Clarke et al, 2015;Molina-Barceló et al, 2014) and in persons aged 60-69 years than in persons aged 50-59 years (Salas et al, 2014). In contrast, adherence to screening among persons with previous participation showed differences by age but not by sex, with lower participation among young men and women, as reported in other studies (Ricardo-Rodrigues et al, 2015;Steele et al, 2010).…”
Section: Accepted Manuscriptsupporting
confidence: 58%
“…Some studies have shown that participation is higher in women than in men (Klabunde et al, 2015;Portillo et al, 2013;Molina-Barceló et al, 2016, Clarke et al, 2015, especially in those aged 50-59 years (Salas et al, 2014).…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…Our estimated FIT sensitivities are at the higher end of those observed in literature. [11][12][13][14] However, the Kaiser Permanente group also reported a sensitivity of 85% in the first screening round and then showed a decrease in sensitivity of 6%-8% in subsequent screening rounds.…”
Section: Discussionmentioning
confidence: 99%
“…7 The European guidelines for quality assurance in colorectal cancer screening states that the participation rate represents a key quality indicator for ensuring effectiveness and efficiency of populationbased screening programmes. 7 However, results from current programmes in Spain show that participation is not reaching these recommended figures, with uptake rates varying from 17.2% to 42.3%, [10][11][12][13][14] with the exception of the Basque Country (64.3%). 14 The uptake rate in the first round for the Colorectal Cancer Screening Program of Barcelona (CCSPB) was 43.6%.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, results from current programmes in Spain show that participation is not reaching these recommended figures, with uptake rates varying from 17.2% to 42.3%, [10][11][12][13][14] with the exception of the Basque Country (64.3%). 14 The uptake rate in the first round for the Colorectal Cancer Screening Program of Barcelona (CCSPB) was 43.6%. 15 Differences in programme organisation, sociodemographics, and primary care professional involvement may explain these differences (for example, the involvement of the GP differs depends on certified training, scheduling of colonoscopy, information feedback, or FIT collection in primary care).…”
Section: Introductionmentioning
confidence: 99%